KEBIJAKAN PEMERINTAH DALAM PENANAMAN NILAI-NILAI ANTI KORUPSI MELALUI KURIKULUM PENDIDIKAN - fatmawati (PELITA NUSA TENGGARA, 2024)
Corruption is an act that is detrimental to the state and the people. Eradicating corruption cannot be resolved simply by hoping for law enforcement in this country. For this reason, preventive measures need to be taken, one of which is through education. The aim of this research is to determine the implementation of government policies in integrating anti-corruption values ​​through educational curricula, the implementation of anti-corruption education in schools, and the role of the Corruption Eradication Commission (KPK) in efforts to prevent corruption from an early age. The research method used in this research is a case study method with data collection techniques through literature review. The data analysis technique used is the Miles and Huberman Model. Based on the research results, it can be seen that the implementation of government policy in instilling anti-corruption values ​​is carried out using several mechanisms starting from the Model activated in all subjects, the Model outside of learning, the Civilization Model, practicing values ​​in all school activities and atmosphere, the combined Model. The Corruption Eradication Commission's form of corruption prevention effort is carrying out anti-corruption outreach and education in schools by involving teachers.